Effects of crawler tractor logging on soil compaction in central Pahang - Jusoff, Kamaruzaman; Nik Ab. Majid, Nik Muhamad (1987)
The effects of crawler tractor logging on soil compaction of a Plinthoxic Tropudults were examined on a mixed hill dipterocarp forest stand in Berkelah Forest Reserve by collecting 7.6cm soil samples to a depth of 12 cm plots randomly established in skid tracks, log-disturbed, berm, bush landing and adjacent undisturbed (control) soils. The data suggest that soil bulk density, total pore space and aeration porosity were not severely altered following crawler tractor logging during dry months when compared to unlogged areas. Saturated hydraulic conductivity was however significantly reduced on bush landing, track and log-disturbed areas but not on the berm and unlogged areas.